KEANEKARAGAMAN JENIS CAPUNG PADA BERBAGAI TIPE HABITAT DI DESA CIPEUTEUY KECAMATAN KABANDUNGAN KABUPATEN SUKABUMI - Alan Wasahlan; Insan Kurnia (Jurnal Biosilampari : Jurnal Biologi, 2022)
Dragonflies are insects that mostly live as nymphs and are related to aquatic habitats and act as bioindicators of environmental quality. The purpose of the study was to identify the diversity of dragonflies in various habitat types in Cipeuteuy Village. This study uses the line transect method measuring 100 meters with a width of 20 meters right and left and the duration of observation is 15 minutes per each observation line. The study was conducted in nite habitat types from 52 locations. The total dragonfly found were 13 species from four families. The highest dragonfly richness was found in the rice field habitat as many as 12 species and the lowest species was found in the citrus garden habitat as many as three species. The dominant species of dragonfly found in all habitat types is Rhodothemis rufa. The overall dragonfly diversity index was 2.56 and ranged from 1.10 to 2.48, and the evenness index ranged from 0.57 to 0.90.